The Effect of Using Communication Strategies on the Achievement of First-Intermediate Female Students and Developing their Motivation to Learn English (Journal of the College of Basic Education, 2022)
The present research aims to identify the effect of using communication strategies on the achievement of first –intermediate female students and developing their motivation to learn English. To achieve the objectives of the study , two null hypotheses have been formed. The research depends on the experimental method with two equivalent groups with the pre-test and post-test. The sample included first grade female students from the left side of Mosul city at Sanaa and Hadbaa intermediate schools. The sample has included (64) female students selected by the researcher intentionally from the study population. The students have been divided into two groups. The first is the (experimental) including (31) female students who are taught by using communication strategies. The second group is the (control group) including (33) female students who are taught according to the traditional method. Equivalence has been made for both study groups in a number of variables that may affect the experimental design of the study, such as(chronological age , intelligence, achievement scores in the first intermediate of English material in the first term ( 2013/2014), the educational attainment of the parents, and the pre- test of the motivation scale). To achieve the aims of the research, the research has required two tools prepared by the researcher: the first tool is represented by the achievement test(oral and written) in EnglishThe oral test reliability was found by using Cronbach's alpha equation. Therefore, the reliability coefficient is(0.82). As for the written test, after verifying the content test validity, The written test reliability was found by using Kuder- Richardson equation (20). Therefore, the reliability coefficient is (0.83). The second tool is represented by the motivation scale (prepared by the researcher) .The scale has finally included (40)items with five alternatives. After verifying the face validity of the scale, its discriminatory power was pointed out for each item.The scale reliability is found by using the re-testing method in which the reliability coefficient is (0.82) and by using Cronbach's alpha in which the reliability coefficient is (0.84). The experiment began on (18/2/2014) and ended on (17/4/2014) i.e. it lasted (8) weeks. The English language teacher taught both groups with follow-up on the part of the researcher.Using the statistical means has shown the following results:1- "There is a statistically significant difference between the average scores of the experimental group, which is taught by using communication strategies and average scores of the control group that is taught by the traditional method in achievement test and for the benefit of the experimental group". A-"There is a statistically significant difference between the average scores of the experimental group which is taught by the using communication strategies and average scores of the control group that is taught by the traditional method in the written test and for the benefit of the experimental group ".B-"There is a statistically significant difference between the average scores of the experimental group taught by using of communication strategies and average scores of the control group that taught by the traditional method in the oral test and for the benefit of the experimental group".2"There is a statistically significant difference between the average scores of the experimental group which is taught by using communication strategies and average scores of the control group that is taught by the traditional method in motivation toward learning English and for the benefit of the experimental group".The results of research the affirm the contribution of communication strategies to the achievement of first –intermediate female students and developing their motivation to learn English. This indicates that learning English by using communication strategies is more favourable to learning than the traditional approaches. In view of the findings obtained , the research ended up with a number of recommendations. Furthermore, some suggestions for further studies are provided as well